Incorporating Quantum Learning Model to Deep Learning Approach in English Language Teaching at MTs Bustanul Ulum, Pujer, Bondowoso - Irfan Masrur; Naily Inayatul Maghfirah (Universitas Maritim Raja Ali Haji (UMRAH), 2026)
This research aims to explore the incorporation of the Quantum Learning Model into the Deep Learning Approach in English Language Teaching (ELT) at MTs Bustanul Ulum, Pujer, Bondowoso. The study employed a descriptive qualitative design to describe and interpret the integration process, the strategies used by the teacher, and the impacts on students’ engagement and understanding. The participants consisted of one English teacher and a group of eighth-grade students selected through purposive sampling. Data were collected through classroom observations, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model involving data reduction, data display, and conclusion drawing. The findings revealed that the incorporation of the Quantum Learning Model into the Deep Learning Approach created a dynamic, engaging, and meaningful learning atmosphere. The Quantum Learning principles, such as positive reinforcement, contextual learning, and multisensory experiences, effectively enhanced students’ motivation and participation. Meanwhile, the Deep Learning Approach encouraged students to think critically, reflect, and apply their knowledge in communicative and contextual ways. The teacher’s role shifted from being a transmitter of knowledge to a facilitator and motivator, guiding students through collaborative and inquiry-based activities. In conclusion, this study demonstrates that incorporating the Quantum Learning Model into the Deep Learning Approach can significantly improve the quality of English instruction by making learning more holistic, enjoyable, and meaningful. It suggests that English teachers adopt this integrated model as an innovative strategy to foster motivation, critical thinking, and lifelong learning attitudes among students.